Pepsinogen I as a marker of risk of gastric mucosal cell destruction in Helicobacter pylori-infected patients taking acetylsalicylic acid - I.G. Paliy; S.V. Zaika; А.G. Каpitun; О.М. Muzychuk (Gastroenterologìa, 2025)
Background. Antiplatelet therapy is a major component of the treatment in patients at high risk of cardiovascular complications. Antiplatelet agents that are used to prevent blood clots can have several adverse effects on the gastrointestinal tract, such as bleeding and ulcers. An additional factor that can lead to the formation of ulcers, which can cause bleeding, is the Helicobacter pylori (Hp) infection. The purpose was to assess the effect of acetylsalicylic acid (ASA) at a dose of 75 mg on the level of pepsinogen I in patients with сardiovascular disease depending on the Hp status and pantoprazole intake. Materials and methods. The level of pepsinogen I was determined in 82 patients who had been taking ASA at a dose of 75 mg over at least 1 year for сardiovascular disease and had not a history of anti-helicobacter pharmacotherapy, among which 40 individuals had been received pantoprazole, a proton pump inhibitor, at a dose of 40 mg/day for at least 1 month as a gastroprotector at the time of referral. Results. In Hp-positive patients who did not take pantoprazole, the level of pepsinogen I was (122.2 ± 10.4) μg/l, in the group of Hp-negative patients who did not receive pantoprazole, the level of pepsinogen I was (89.7 ± 5.4) μg/l. In Hp-positive and Hp-negative individuals who took pantoprazole, the levels of pepsinogen I were (96.1 ± 6.8) μg/l and (86.6 ± 5.4) μg/l, respectively. A comparative analysis showed that in patients who took only ASA at a dose of 75 mg and were Hp-negative, the level of pepsinogen was significantly lower (p < 0.003) than in those who also took only ASA at a dose of 75 mg and were Hp-positive. According to the results of ROC curve analysis, the best cutoff point for the level of pepsinogen I, at which the risk of damage to the gastric mucosa appears, is > 125.4 μg/l (sensitivity 77.3 % (95% CI: 54.6–92.2), specificity 95.0 % (95% CI: 75.1–99.9), AUC 0.785 ± 0.080; p < 0.001). We found a significant inverse correlation (p < 0.01) between the level of pepsinogen I and the incidence of Hp infection. The correlation coefficient was –0.53 indicating a moderate relationship between the studied parameters. No significant differences (p > 0.05) were found in the level of pepsinogen I between Hp-negative and Hp-positive patients who took ASA at a dose of 75 mg and pantoprazole at a dose of 40 mg. When comparing Hp-positive groups who received only ASA and patients who took ASA and pantoprazole, a significant decrease (p < 0.04) in the level of pepsinogen I was found. The levels of pepsinogen I in such groups were (122.2 ± 10.4) μg/l versus (96.1 ± 6.8) μg/l, respectively. No significant differences (p > 0.05) were found in the level of pepsinogen I between the Hp-negative groups of patients: individuals who took only ASA and those who took ASA and pantoprazole. Pepsinogen I levels in these groups were (89.7 ± 5.4) μg/L versus (86.6 ± 5.4) μg/L, respectively. Conclusions. The presence of Hp infection in patients receiving ASA even in low doses (75 mg) is a risk factor for a significant increase (p < 0.003) in the level of pepsinogen I. Taking pantoprazole significantly reduces (p < 0.04) the level of pepsinogen I (a marker of destruction of the gastric mucosa) in Hp-infected patients receiving ASA in low doses (75 mg). Thus, pantoprazole can be considered the drug of choice in this category of patients.